“Your Head so Dear to my Heart, I Would Hug Tight to My Chest and I would Tell How Much I Love You”. Letters of Jozefina Hálkova to Czesław Jankowski from 1884 - Fedorovič, Irena (Slavistica Vilnensis, 2019)
The aim of the article is to analyze the three letters written in Czech in 1884 and addressed to Polish poet, writer, literature critic, and translator Czesław Jankowski (1857–1929). The author of the letters is a previously unknown Czech woman, the daughter of a schoolteacher in the city of Kladno. She got acquainted with Cz. Jankowski in Krakow and became the object of his passion. The letters are stored in the Wroblewski Library of the Lithuanian Academy of Sciences in Vilnius. Although the author of this article has already mentioned the existence of these love letters in 2000, J. Hálkova’s letters to Cz. Jankowski have not yet been analyzed.
Keywords: Jozefina Hálkova; Czesław Jankowski; love letters; late 19th century